Graph Models of Harems and Tournaments in Sports Clubs - Mochamad Suyudi (Research Collaboration Community (RCC), 2022)
By looking at the extension of Hall's marriage theorem to harems, where some people are allowed to have more than one partner, Traditionally in harems any man can have multiple wives but no woman can have more than one husband. then consider the different types of matches by looking at 'round robin tournaments' in sports clubs. An unexpected connection between the two worlds emerged when we were able to use our harem results to deduce theorems about the tournament.